The Impact of the COVID-19 Pandemic on Women’s Reproductive Health - Phelan, Niamh; Behan, Lucy Ann; Owens, Lisa (Frontiers in Endocrinology, 2021)
Background: The Covid-19 pandemic has profoundly affected the lives of the global population. It is known that periods of stress and psychological distress can affect women’s menstrual cycles. We therefore performed an observational study of women’s reproductive health over the course of the pandemic thusfar. Materials/methods: An anonymous digital survey was shared via social media in September 2020. All women of reproductive age were invited to complete the survey. Results: 1031 women completed the survey. Mean age was 36.7 +- 6.6 years. 693/70% reported recording cycles using an app or diary. 233/23% were using hormonal contraception. 441/46% reported a change in their menstrual cycle since the beginning of the pandemic. 483/53% reported worsening premenstrual symptoms, 100/18% reported new menorrhagia (p=0.003) and 173/30% new dysmenorrhea (p<0.0001) compared to before the pandemic. 72/9% reported missed periods who not previously missed periods (p=0.003) and the median number of missed periods was 2 (1-3). 17/21% of those who ‘occasionally’ missed periods pre-pandemic missed periods ‘often’ during pandemic. 467/45% reported a reduced libido. There was no change in the median cycle length (28 days) or days of bleeding (5) but there was a wider variability of cycle length (p=0.01) and a 1 day median decrease in the minimum (p<0.0001) and maximum (p=0.009) cycle length. Women reported a median 2kg increase in self-reported weight and a 30 minute increase in median weekly exercise. 517/50% of women stated that their diet was worse and 232/23% that it was better than before the pandemic. 407/40% reported working more and 169/16% were working less. Women related a significant increase in low mood (p<0.0001), poor appetite (p<0.0001), binge eating (p<0.0001), poor concentration (p<0.0001), anxiety (p<0.0001), poor sleep (p<0.0001), loneliness (p<0.0001) and excess alcohol use (p<0.0001). Specific stressors reported included work stress (499/48%), difficulty accessing healthcare (254/25%), change in financial (201/19%) situation, difficulties with home schooling (191/19%) or childcare (99/10%), family or partner conflict (170/16%), family illness or bereavement (156/15%). Conclusions: The Covid-19 pandemic has significantly impacted the reproductive health of women. The long term health implications of this are yet to be determined and future studies should address this